А look throuch time: memories as an artistic form of representation of memory in the novels “The Land of bitter tenderness” by Volodymyr Lys and “Recent stories” by Olga Tokarchuk (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2025)
The article examines the novels of the most popular writers of Ukraine and Poland - “The Land of Bitter Tenderness” by Volodymyr Lys and “Recent Stories” by Olga Tokarchuk in the context of preserving ancestral and national memory, represented through the form of memories. The deconstruction of the past in both works takes place through the memories of three women (grandmothers - daughters - grandchildren). Overlapping with the events of the present, memories expand the space-time continuum of the work through retrospection and prospecting. The focus is on the correlation of individual and collective memory, represented in a number of stories set out in the novels. During the analysis, studies in culturology, psychology, sociology, philosophy A. Assman, J. Assman, P. Nora, R. Terdiman and others were used. It is stated that the individual memory of a person as the most important dimension of his existence in the epic is developed through the ancestral memory, which is superimposed on the historical memory of the people. The space of memory in the text is marked by various forms of information storage and creates a horizon of living memory. In the novels the concept of memory is understood on an individual, social, cultural, national, and historical level. The individual memory of older women is combined with the historical trauma of IDPs and children of “enemies of the people”. Genetic memory becomes the matrix of the identities of Dazdraperma - Vitaly - Olesya (“The Land of Bitter Tenderness”) and Paraskeva - Ida - Maya (“Recent Stories”). The markers of this memory in the works are the Ukrainian language and religiosity. Ukrainian and Polish works bring together the form of the story, the theme of memory, the recurrence of women’s destiny, loneliness, maternal instinct, national identity. Three women’s destinies are a symbolic projection of a man against the background of historical events of the 20th century in Poland and Ukraine.
Keywords: Volodymyr Lys; Olga Tokarchuk; memories; individual memory; collective memory; women’s destiny; identity; history